Efficacy of Ammonium Chloride and Horse Gram (Dolichos Biflorus) extract on the amelioration of Urolithiasis in Goats - Senthilkumar R P (Department of Animal Nutrition, College of Veterinary and Animal Sciences, 1998)
The efficacy of ammonium chloride and horse gram (Dolichos biflorus) extract on the amelioration of urolithiasis in goats ware evaluated by using 18 male Malabari goats of 9 to 12 months old, maintained for an experimental period of 84 days. Goats were divided into three groups (I, 11 and Ill) of six animals each and were fed individually at maintenance level with high magnesium basal calculogenic ration containing 1.194 per cent calcium, 0.578 per cent phosphorus, 1.202 per cent magnesium (ration A) alone, fortified with ammonium chloride at the rate of one per cent in the ration (ration B) or with supplemented horse gram extract at the rate of one litre per animal per day (ration C) respectively. Grass and concentrate were fed at 1: 4 ratio and drinking water provided ad libitum throughout the experiment. Body weight gain, dry matter intake, feed efficiency and protein efficiency were not significantly altered by the dietary treatments, b.ut. goats fed on supplemental ammonium chloride (group 11) had a trend towards better weight gain, feed and protein efficiency. •No significant difference observed among the three groups with regard to TEC, TLC, haemoglobin, and plasma protein. Elevated dietary magnesium in the diet (ration A) caused significant decrease in serum